EVALUATION OF VARIOUS POTATO CULTIVARS OF JAMMU REGION FOR PROCESSING ATTRIBUTES - RESHI, MONICA; BHAT, ANJU; KAUL , RAJ KUMARI; GUPTA, MONI (The Bioscan, 2013)
Potato tubers of six varieties viz., Kufri Jyoti, Kufri Sindhuri, Kufri Badshah, Kufri Chandermukhi, Kufri ChipsonaI and Kufri Chipsona-II were stored at room temperature (22-38°C, RH 37-80%) after harvest and evaluated for their losses due to rottage, sprouting weight loss and chemical composition. Kufri Chandermukhi and Kufri Chipsona II were found to be the best, since they have the highest amount of specific gravity (0.78%,0.79%) each, Dry matter content (18.23%,17.84%), and Crude fiber (0.49%,0.40%) respectively. From the above values Kufri Chipsona-II was considered best for the development of chips and Kufri Chandermukhi for the development of flour. The finding of the study suggests that 60 days storage of potatoes at normal temperature with proper ventilation could be explored for storing processing potatoes